Automation tool to deploy Simulink models into Programmable System-on-Chip - Almeida, Alexandre A. A. de [UNESP] (2016)
In this article we present a computational tool called MS2PSoC to automate the deployment of applications developed in Matlab/Simulink environment in PSoC hardware. The purpose of this automation is to assist the project development process described in Simulink and translated to PSoC Creator environment. The proposed methodology is to translate the digital or analog designs described in the Matlab/Simulink environment to programming language and hardware supported by PSoC hardware. Two case studies were used to assess the proposed methodology. The first case it is a digital case consisting of the MLT-3 line code. The second case is reported to a D/A converter of 4 bits employing the model Ladder R-2R. Both cases have been described in Simulink environment and then implemented in hardware PSoC using the MS2PSoC tool. The results show the feasibility of the methodology developed in the tool.